Empowering staff in dementia long-term care: towards a more supportive approach to interventions - Figueiredo, Daniela (2013)
This pilot-study aimed to assess a psychoeducational program for staff in care homes. The program was designed to increase knowledge regarding dementia care, promote skills to integrate motor and multisensory stimulation in daily care, and develop coping strategies to manage emotional work-related demands. Six staff members received eight psychoeducational sessions held fortnightly and individualized assistance during the provision of morning care to six residents with dementia. An audio-recorded focus group interview with staff and video recordings of residents' behavior during morning care were made and used to assess the program. Staff reported several benefits: acquisition of new knowledge; demystification of preexisting beliefs related to dementia; group cohesion; self-worth feelings; and positive coping. A trend towards improvements at residents' levels of interaction was found. The findings suggest the need of interventions to go beyond the objectives exclusively centered on staff education and the promotion of residents' well-being. This should be achieved by also allowing workers to feel supported and empowered.